A dimensão criativa de Radamés Gnattali no ciclo Brasilianas - Lucas Pimentel Telles (2017)
This research presents a study of the creative practices of Radamés Gnattali, focusing on the parts that make up the Brasilianas cycle. Biographical information from the composer and the focus pieces was collected, as well as musical analysis, critical editing and arrangement. During the work with the Brasilianas, reflections were made that surround the creative environment of the cycle and the composer.